ANALYSIS OF BALANCED SCORECARD PERSPECTIVE IN PRIVATE COLLEGE MANAGEMENT AS A BASIC OF LECTURER PERFORMANCE ASSESMENT (Case Study of Computer Science College of Binaniaga) - Ismulyana Djan (The Management Journal of Binaniaga, 2018)
The application of Balanced Score in a college institution especially lecturer performance is a new case, Computer Science College of Binaniaga is one that applies and utilizes this knowledge to develop strategic planning, implement and evaluate using balanced scorecard, the research is based on the implementation of the balanced scorecard theory developed by Kaplan and Norton through a case study at STIKOM Binaniaga college, the result of the study can illustrate that researchers can develop a strategy map and plan the balanced scorecard performance of STIKOM Binaniaga lecturers, where four balanced scorecard perspectives with several strategy targets at each perspective are measured by each strategy objective and target to be achieved will be easily implemented, this is to provide very clear information to the management of universities, that each perspective can be implemented well in accordance with the needs of colleges in terms of conducting performance appraisals of lecturers at Computer Science College of Binaniaga (STIKOM Binaniaga). Keyword: Balanced Scorecard, Perspective